2023
DOI: 10.1073/pnas.2216308120
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes rescuing protein folding

Abstract: Maintaining the health of the proteome is a critical cellular task. Recently, we found G-quadruplex (G4) nucleic acids are especially potent at preventing protein aggregation in vitro and could at least indirectly improve the protein folding environment of Escherichia coli . However, the roles of G4s in protein folding were not yet explored. Here, through in vitro protein folding experiments, we discover that G4s can accelerate protein folding by rescuing kinetically trapped intermediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Similar to many other fluorescent proteins, TagRFP675 exhibits a slow maturation time (Balleza et al, 2018), resulting in kinetically trapped intermediates and poor folding in E. coli (Son et al, 2023). With the assistance of molecular chaperones, such as GroEL, TagRFP675 can overcome kinetic barriers to fold properly in E. coli (Son et al, 2023). Therefore, we used TagRFP675 to further investigate whether the reporter activity of the intein biosensor is correlated with the folding status of POI in the presence or absence of GroEL (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to many other fluorescent proteins, TagRFP675 exhibits a slow maturation time (Balleza et al, 2018), resulting in kinetically trapped intermediates and poor folding in E. coli (Son et al, 2023). With the assistance of molecular chaperones, such as GroEL, TagRFP675 can overcome kinetic barriers to fold properly in E. coli (Son et al, 2023). Therefore, we used TagRFP675 to further investigate whether the reporter activity of the intein biosensor is correlated with the folding status of POI in the presence or absence of GroEL (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…As ROS and other protein stresses accumulate with age and according to APOE genotype, rG4s form. Although rG4s can rescue protein folding and could release proteins when unfolded at stress cessation 32 , under persistent stress proteins would not be released from the G-quadruplexes, leading to increased protein oligomerization and aggregation 20 . This function has previously been suggested for RNA in biomolecular condensates more generally 33 .…”
Section: Discussionmentioning
confidence: 99%
“…79 Additionally, G-quadruplex-forming sequences assisted in the folding of a protein folding biosensor, TagRFP675 in cells. 80 TagRFP675 does not fold well in E. coli without cooverexpressing a chaperone (such as GroEL or DnaK). Gquadruplex forming sequences had similar protein-folding activity compared to chaperone controls, demonstrating that G-quadruplexes enhanced protein folding in cells.…”
Section: Emergence Of Nucleic Acids As Chaperonesmentioning
confidence: 99%
“…79 In vitro assays with chemically denatured TagRFP675 and Gquadruplexes revealed that G-quadruplexes rescued kinetically trapped intermediates to restore TagRFP675 fluorescence. 80 To further explore the mechanism behind the G-quadruplex chaperone activity, two chaperone G-quadruplex sequences with solved NMR structures were systematically mutated. Single-point mutations were able to dramatically affect chaperone activity in either a positive or negative sense.…”
Section: Emergence Of Nucleic Acids As Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation